Analisa Sistem Pengendalian Manajemen pada Penjualan Usaha Daster Dasby’D - Sheila Permatasari Eliso; Rizka Maulida Arinanda; Fitri Nur Aini; Amin Sadiqin (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
The goal of this study is to gain knowledge and understanding of how Dasby'D's business uses the sales management control system. Dasby'D is a company that sells women's pajamas and daster clothing. As part of its business process, it purchases daster in large amounts and at wholesale prices in order to produce high-quality products at prices that can be afforded by all layers of society. Dasby'D prepares an operational budget as part of its operational activities with the goal of informing business owners about their expected performance. In order to reach the level of sales and generate profit or profit, a company's operating budget must be determined and ensured by the management control system. Deductive analysis methods and descriptive analysis methods are used in the data analysis technique. The results of the research show that Dasby'D's efforts were successful in limiting the amount of cash used for financing and the purchase of goods. One of the performance criteria for businesses receiving a return of about 20% of revenue is profit acquisition. This indicates that the business is operating at a level of performance that is comparable with a company that has seen growth in a good and positive direction.